IMPLEMENTASI PROGRAM PEMBIAYAAN ULTRA MIKRO PADA KANTOR PELAYANAN PERBENDAHARAAN NEGARA DI KABUPATEN SINJAI - Amra, Musthaofiah; Usman, Jaelan; Yusuf, Muhammad (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
The purpose of this study was to determine the implementation of the ultra-micro financing program at the state treasury service office in Sinjai district. The method used in this study is a qualitative method which explains how the implementation of the ultra-micro financing program at the state treasury service office in Sinjai district is used. The research informants were 10 people. Research information was collected through observation, interviews and documentation. The results showed that the implementation of the ultra-micro financing program at the state treasury service office in Sinjai district, seen from the resources, had distributed optimally and evenly for business actors who had not been touched by banks with good capital assistance. in terms of human as well as financial and time. Furthermore, judging from the attitude (disposition) of the implementers are good, but in the economic, social and political environment there are supporting factors and several obstacles in the distribution of ultra micro.